2014
DOI: 10.1182/blood-2013-06-509794
|View full text |Cite
|
Sign up to set email alerts
|

IKZF1 status as a prognostic feature in BCR-ABL1–positive childhood ALL

Abstract: Key Points• IKZF1 deletions are predictive of an unfavorable outcome in childhood BCR-ABL1-positive ALL.• Good-risk BCR-ABL1-positive patients with wild-type IKZF1 have good outcomes when treated with imatinib.Childhood BCR-ABL1-positive B-cell precursor acute lymphoblastic leukemia (BCP-ALL) has an unfavorable outcome and shows high frequency of IKZF1 deletions. The prognostic value of IKZF1 deletions was evaluated in 2 cohorts of BCR-ABL1-positive BCP-ALL patients, before tyrosine kinase inhibitors (pre-TKI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
106
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(120 citation statements)
references
References 32 publications
(59 reference statements)
5
106
0
Order By: Relevance
“…Despite this low mutational load, key pathways are mutated at high frequency across multiple subtypes of ALL, including: (1) 13 In contrast, alterations of IKZF2 (HELIOS) and IKZF3 (AIOLOS) are selectively associated with near haploid and low hypodiploid ALL, but are otherwise rare in non-hypodiploid ALL. 4 …”
Section: Recurring Alterations Of Multiple Key Pathways In Allmentioning
confidence: 99%
“…Despite this low mutational load, key pathways are mutated at high frequency across multiple subtypes of ALL, including: (1) 13 In contrast, alterations of IKZF2 (HELIOS) and IKZF3 (AIOLOS) are selectively associated with near haploid and low hypodiploid ALL, but are otherwise rare in non-hypodiploid ALL. 4 …”
Section: Recurring Alterations Of Multiple Key Pathways In Allmentioning
confidence: 99%
“…Although the Ph chromosome in ALL is associated with a poor prognosis, treatment with tyrosine kinase inhibitors have improved the event free survival rates of ALL patients compared to patients treated with traditional chemotherapy and stem cell transplantation [17,18]. However, Phpositive ALL with IKZF1 deletions has an unfavourable outcome even with imatinib therapy compared to those with IKZF1 wild-type [19,20]. Gene expression profiling (GEP) has also identified 'BCR-ABL1-like' B-ALL which is found in 15% of childhood B-ALL.…”
Section: A) Primary Chromosomal Abnormalities (I) Chromosomal Translomentioning
confidence: 99%
“…1,2 In several studies, deletions of IKZF1-encoding IKAROS, a transcription factor important for lymphoid development and differentiation-have been associated with a poor treatment outcome in precursor B cell ALL. [3][4][5] Deletions of IKZF1 are observed in 10-15% of pediatric ALLs and affect either the entire IKZF1 gene or appear as focal deletions. [3][4][5] The most common of the latter ones (Δ4-7) includes the DNA-binding region and results in a dominant-negative isoform (Ik6), impairing cell differentiation in CD34+ lymphoid progenitor cells.…”
mentioning
confidence: 99%
“…[3][4][5] Deletions of IKZF1 are observed in 10-15% of pediatric ALLs and affect either the entire IKZF1 gene or appear as focal deletions. [3][4][5] The most common of the latter ones (Δ4-7) includes the DNA-binding region and results in a dominant-negative isoform (Ik6), impairing cell differentiation in CD34+ lymphoid progenitor cells. [3][4][5] Recently, Clappier et al 6 from the EORTC Study Group suggested that patients with IKZF1-deleted ALL and intermediate-risk features-so-called average-risk (AR) patientstreated on the BFM-based EORTC protocol 58951 may benefit from intensification of conventional maintenance therapy by application of vincristine-glucocorticoid pulses.…”
mentioning
confidence: 99%
See 1 more Smart Citation